Effect of Concept Attaiment Education Model for Vocabulary Promotion for Seventh Grade Students in TPI High School Padang Hunik - Lasmina, Lenni; Dewi, Yelfi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
One of the research problems that occur in teaching vocabulary in this school is that the level of vocabulary mastery of students is still low, students' enthusiasm in teaching vocabulary, and students are less interested in teaching vocabulary. The aim of this research is to apply the Concep Attaiment learning model of achievement in the seventh grade at Padang TPI Hunk High School North Sumatra. This scientific research is quantitative research. This scientific research uses True Experimental with the Type of Control Group Design model with pre- and post-testing with one type. The results of the research found the effect of the Concept Attaiment education model to upgrade the vocabulary of seventh grade students. This appeared from the results of the post-test in the control class with an average value of 71.25. The average value in the experimental semester is 85.5. Based on the sig (2-tailed) hypothesis test which is 0.000.Smaller than 0.005 is Ha acceptable means there is an impact of the Concept Attaiment education model to upgrade the vocabulary of seventh graders at TPI High School Padang Hunk North Sumatra.